Perbedaan Kecemasan Pasien Sebelum dan Sesudah Diberikan Spiritual Emotional Freedom Technique di Ruang IGD RSUD dr Gondo Suwarno: The Differences in Anxiety of Psychosomatic Patients Before and After Being Given the Spiritual Emotional Freedom Technique in the Emergency Room of RSUD Dr Gondo Suwarno - Ani Sri Setyo Wijianti; Eko Susilo (Journal of Holistics and Health Sciences (JHHS), 2023)
The overcrowding of patients and procedures has the potential to increase pain, discomfort and threaten the integrity of the body causing patient anxiety in the emergency room. Anxiety in emergency room patients that is not handled properly can contribute to the morbidity and death of critically ill patients. Therapy that uses spiritual elements is safe, easy, fast and simple, even without risk because it does not use tools or needles to reduce anxiety problems, including the Spiritual Emotional Freedom Technique (SEFT). To find out the difference in the anxiety of psychosomatic patients before and after being given the SEFT in the emergency room of RSUD Dr Gondo Suwarno. The design of this study used a pre-experimental approach with a one group pre-post test design approach. The population studied was the psychosomatic patient in the Emergency Room at Dr. Hospital. Gondo Suwarno, as many as 557 people with a total sample of 10 people were taken using purposive sampling technique. The data analysis used was paired sample t-test which was processed using the SPSS data processing program. The anxiety of psychosomatic patients before being given the spiritual emotional freedom technique was mostly in the category of severe anxiety (70,0%). The anxiety of psychosomatic patients after being given the spiritual emotional freedom technique was mostly in the category of severe anxiety (70,0%). There is a significant difference in the anxiety of psychosomatic patients before and after being given the spiritual emotional freedom technique in the emergency room of RSUD Dr Gondo Suwarno, obtained a p-value of 0,000 <0,05 (α). It is better for patients in the emergency room to follow all the instructions given by the nurse when giving the spiritual emotional freedom technique so that optimal results are obtained, namely the anxiety experienced can be controlled immediately. ABSTRAK Kepadatan pasien dan prosedur tindakan berpotensi meningkatkan nyeri, ketidaknyamanan dan mengancam integritas tubuh menyebabkan kecemasan pasien di ruang IGD. Kecemasan pada pasien IGD yang tidak tertangani dengan baik maka dapat berkontribusi pada morbiditas dan kematian pasien saat kritis. Terapi yang menggunakan unsur spiritual aman, mudah, cepat dan sederhana bahkan tanpa risiko karena tidak menggunakan jarum untuk mengurangi kecemasan diantaranya Spiritual Emotional Freedom Technique (SEFT). Tujuan penelitian ini untuk mengetahui perbedaan kecemasan pasien sebelum dan sesudah diberikan spiritual SEFT di ruang IGD RSUD Dr Gondo Suwarno. Desain pada penelitian ini menggunakan pre eksperimen dengan pendekatan one group pre-post test design. Populasi yang diteliti pasien instalasi Gawat Darurat Rumah Sakit Dr. Gondo Suwarno, sebanyak 557 orang dengan jumlah sampel 10 orang diambil dengan mengunakan teknik purposive sampling. Analisis data yang digunakan adalah paired sample t-test yang diolah dengan menggunakan program SPSS. Kecemasan pasien sebelum diberikan SEFT sebagian besar kategori cemas berat (70,0%). Kecemasan pasien sesudah diberikan SEFT sebagian besar kategori cemas berat (70,0%). Ada perbedaan yang bermakna kecemasan pasien sebelum dan sesudah diberikan spiritual emotional freedom technique di ruang IGD RSUD Dr Gondo Suwarno, didapatkan p-value sebesar 0,000 < 0,05 (α). Sebaiknya pasien di ruang IGD mengikuti semua instruksi yang diberikan perawat saat memberikan SEFT sehingga diperoleh hasil optimal yaitu kecemasan yang dialami segera dapat terkendali.